DESAIN USER INTERFACE APLIKASI “SWAPLT” SEBAGAI E-COMMERCE BAGI GENERASI Z UNTUK MENGURANGI LIMBAH FESYEN THRIFT IMPOR - Putri, Nabila Tiara (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
Swalpt's user interface design aims to produce a prototype e-commerce application specialised in buying and renting thrift clothing from individuals for Generation Z. This application is expected to become a forum for local thrift clothing transactions and reduce the purchase of illegal imported thrift clothing at flea markets. This application is expected to become a forum for local thrift clothing transactions and reduce the purchase of illegally imported thrift clothing at flea markets. This user interface design uses the Design Thinking framework which includes five stages: empathise, define, ideate, prototype, and test. The research method used is a mixed method involving quantitative and qualitative data. The results of the prototype testing show that this application is visually appealing and easy to use. However, there are still some suggestions for improvements related to usability to make the user experience more comfortable.